Impaired Executive Function and Depression as Independent Risk Factors for Reported Delirium Symptoms: An Observational Cohort Study Over 8 Years - Mychajliw, Christian; Herrmann, Matthias L.; Suenkel, Ulrike; Brand, Katharina; von Thaler, Anna-Katharina; Wurster, Isabel; Yilmaz, Rezzak; Eschweiler, Gerhard W.; Metzger, Florian G. (Frontiers in Aging Neuroscience, 2021)
Background: Acute medical illnesses, surgical interventions, or admissions to hospital in the older individuals are frequently associated with a delirium. In this cohort study, we investigated the impact of specific cognitive domains and depression before the occurrence of delirium symptoms in an eight-year observation of older non-hospitalized individuals. Methods: In total, we included 807 participants (48 – 83 years). Deficits in specific cognitive domains were measured using the CERAD test battery, depressive symptoms using Beck Depression Inventory and the Geriatric Depression Scale before the onset of a delirium. Delirium symptoms were retrospectively assessed by a questionnaire based on the established Nursing Delirium Screening Scale. Results: Fifty-eight of 807 participants (7.2%) reported delirium symptoms over the eight-year course of the study. 69% (n = 40) of reported delirium symptoms were related to surgeries. In multivariate regression analysis, impaired executive function was an independent risk factor (p = 0.034) for the occurrence of delirium symptoms. Furthermore, age (p = 0.014), comorbidities (captured by Charlson comorbidity index) (p < 0.001) and depression (p = 0.012) were significantly associated with reported delirium symptoms. Conclusion: Especially prior to elective surgery or medical interventions, screening for impaired executive function and depression could be helpful to identify patients who are at risk to develop delirium symptoms.